Matera European Photography, Matera Diffusa, Canon Europe Matera for Visions from Europe - Panayides, Angelos (My University, 2026)
Twenty eight students stayed in Matera, together with their professors from the most important schools of Photography all over Europe and carried out a research through photography, to create our own original project. All our selected work produced with the student Anthousa Papadopoulou will be exhibited in several parts of the city of Matera in September 2019 and published in the official referred catalogue.